Noncoding RNA profiling in omentum adipose tissue from obese patients and the identification of novel metabolic biomarkers - Zhang, Yongjiao; Chen, Ao; Lu, Sumei; Liu, Dong; Xuan, Xiaolei; Lei, Xiaofei; Zhong, Mingwei; Gao, Fei (Frontiers in Genetics, 2025)
BackgroundObesity, a prevalent metabolic disorder, is linked to perturbations in the balance of gene expression regulation. Noncoding RNAs (ncRNAs), including long noncoding RNAs (lncRNAs), circular RNAs (circRNAs), and microRNAs (miRNAs), play pivotal roles in regulating gene expression. The aim of this study was to identify additional ncRNA candidates that are implicated in obesity, elucidating their potential as key regulators of the pathogenesis of obesity.MethodsWe identified distinct ncRNA expression profiles in omental adipose tissue in obese and healthy subjects through comprehensive whole-transcriptome sequencing. Subsequent analyses included functional annotation with GO and KEGG pathway mapping, validation via real-time quantitative polymerase chain reaction (qRT‒PCR), the exploration of protein‒protein interactions (PPIs), and the identification of key regulatory genes through network analysis.ResultsThe results indicated that, compared with those in healthy individuals, various lncRNAs, circRNAs, and miRNAs were significantly differentially expressed in obese subjects. Further verifications of top changed gene expressions proved the most genes’ consistence with RNA-sequencing including 11 lncRNAs and 4 circRNAs. Gene network analysis highlighted the most significant features associated with metabolic pathways, specifically ENST00000605862, ENST00000558885, and ENST00000686149. Collectively, our findings suggest potential ncRNA therapeutic targets for obesity, including ENST00000605862, ENST00000558885, and ENST00000686149.